HISTAMINES AND FOODS: A REVIEW ON IMPORTANCE, DETECTION AND CONTROLLING IN FOODS - Mahmoudi, R.; Mardani, K. (Malaysian Journal of Science, 2015)
Biogenic amines are basic nitrogenous compounds that are generated in the course of microbial, vegetable, and animal metabolism. These compounds are found in varying concentrations in a wide range of food including fish, cheese, meat, wine, beer, vegetables, and chocolate. Although the biogenic amines play a number of important physiological functions in the human and animal bodies, its high level can have toxic effects on human and animal’s organs. High amount of amines can be produced by bacteria during amino acids decarboxylation and have been identified as one of the important agent causing seafood intoxication. The most frequent food borne biogenic amine induced health issues is caused by histamine. Various analytical techniques have been used to determine the concentration of biogenic amines including chromatography, enzymatic methods and commercial kits based on immunoassay methods. Temperature is the main factor to control biogenic amine formation in food. A variety of techniques can be combined together to control the microbial growth and enzyme activity during processing and storage for better shelf life extension and food safety. Keywords: Biogenic amines, Food poisoning, Histamine